2013
DOI: 10.1038/sj.bdj.2013.1141
|View full text |Cite
|
Sign up to set email alerts
|

Facial cutaneous sinuses of dental origin – a diagnostic challenge

Abstract: It is common for practitioners to misdiagnose the cause of facial cutaneous sinus tracts, failing to recognise that many have an odontogenic cause. Chronic infection around the apex of a dental root can drain to the mouth or less commonly to the skin via a sinus tract. Dental symptoms are not always present and this confuses the clinical picture further. Failure to identify an odontogenic cause may result in unnecessary and ineffective treatment. Elimination of dental infection via tooth extraction or root can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
93
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(94 citation statements)
references
References 14 publications
1
93
0
Order By: Relevance
“…A study published by Miri et al [13] which was realized in Iran in 1,527 patients with a personal history of endodontic treatment, it was found a frequency of a sinus tract of 9.9% in contrast with another study reported by Sadeghi et al [14] in 2011 in a very similar population with the same procedence and under canalicular therapy, in 728 patients it was set a prevalence of 14.7% [13,14] submitting the patient to unnecessary antibiotic treatments, biopsies, resections, and even radiotherapy, with a not so favorable outcome and a recurrence of the fistula [1][2][3]. Patients with or cutaneous fistulas it has been thought that odontocutaneous fistulas are more frequent in children and adolescents, due to the fact that the alveolar processes are not fully developed, although, it has been seen in patients older than 20 years of age [9]. The average of the patient age varies: Sadeghi et al [14] reported an age range of 10-69 years; in the Guevara et al [15] study the mean was 45 years with a higher presentation of sinus tracts in patients older than 51 years.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A study published by Miri et al [13] which was realized in Iran in 1,527 patients with a personal history of endodontic treatment, it was found a frequency of a sinus tract of 9.9% in contrast with another study reported by Sadeghi et al [14] in 2011 in a very similar population with the same procedence and under canalicular therapy, in 728 patients it was set a prevalence of 14.7% [13,14] submitting the patient to unnecessary antibiotic treatments, biopsies, resections, and even radiotherapy, with a not so favorable outcome and a recurrence of the fistula [1][2][3]. Patients with or cutaneous fistulas it has been thought that odontocutaneous fistulas are more frequent in children and adolescents, due to the fact that the alveolar processes are not fully developed, although, it has been seen in patients older than 20 years of age [9]. The average of the patient age varies: Sadeghi et al [14] reported an age range of 10-69 years; in the Guevara et al [15] study the mean was 45 years with a higher presentation of sinus tracts in patients older than 51 years.…”
Section: Discussionmentioning
confidence: 99%
“…Vicentii, orphyromonas gingivalis Veillonella parvula, Enterococcus faecalis, Campylobacter gracellis and Neisseria mucosa invade the tooth through the enamel and dentin, infecting the pulp causing necrosis, periodontitis and formation of the periapical abscess, rich in anaerobic bacteria. Usually this process is acute and renders the patient to seek medical attention [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. With the passing of time between six months and 30 years, added to the partial and temporal recovery, symptoms may be masked meanwhile the infectious process continues and intensifies, becoming chronic.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations